2003
DOI: 10.3354/meps251127
|View full text |Cite
|
Sign up to set email alerts
|

Role of physical disturbance in structuring fish assemblages in seagrass beds in Port Phillip Bay, Australia

Abstract: Disturbance in seagrass habitats may cause variation in the structure of fish assemblages and individual taxa. One important form of disturbance is wave action associated with strong winds. Total fish abundance and species richness from seagrass beds at 2 sites in Port Phillip Bay, Australia, were sampled during low and high wave disturbance. During high wave action (> 0.25 m) in seagrass beds, abundance of fish at one site decreased significantly, but species richness was unaffected at both sites. Plankton sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 60 publications
(72 reference statements)
1
17
0
Order By: Relevance
“…During calm weather conditions associated with offshore winds, recapture rates were lower, and numbers of recaptured fish showed no difference amongst cage sides. The net movement of fish offshore during rough weather conditions is consistent with previous studies conducted at this site, when fewer post-larval S. punctata were collected in the seagrass during high wave/ onshore wind conditions (Jenkins et al 1997, Moran et al 2003. From these results we suggest that episodic disturbance events operating over relatively short temporal scales, for example high-wave conditions generated by onshore winds, have the potential to reentrain post-larvae into the plankton, thereby facilitating secondary dispersal.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…During calm weather conditions associated with offshore winds, recapture rates were lower, and numbers of recaptured fish showed no difference amongst cage sides. The net movement of fish offshore during rough weather conditions is consistent with previous studies conducted at this site, when fewer post-larval S. punctata were collected in the seagrass during high wave/ onshore wind conditions (Jenkins et al 1997, Moran et al 2003. From these results we suggest that episodic disturbance events operating over relatively short temporal scales, for example high-wave conditions generated by onshore winds, have the potential to reentrain post-larvae into the plankton, thereby facilitating secondary dispersal.…”
Section: Discussionsupporting
confidence: 80%
“…However, it was not possible to distinguish between dispersal through resuspension or mortality. Moran et al (2003) have recently suggested that secondary dispersal is a possible mechanism accounting for the significant reduction of post-larvae collected in seagrass beds during increased physical disturbance, although mortality through physical injury caused by wave action was also discussed. However, the present study has shown that mortality driven by physical injury cannot account for variability in post-larval abundance during physical disturbance associated with rough weather.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of their close proximity to the shore, seagrass beds are extremely susceptible to natural (Holbrook et al 2002b, Moran et al 2003 and anthropogenic (Bell et al 2002) disturbances that result in thinning, fragmentation, and habitat loss. Surfgrasses are subject to high wave energy from storms and large swells (Holbrook et al 2002b, Bull et al 2004) that may result in their removal; in some instances, much of an entire bed may be lost (e.g.…”
Section: Introductionmentioning
confidence: 99%